Estimasi Volume Air Waduk Lau Kawar Menggunakan Pendekatan Integral Volume Kulit Tabung - Rizka Nabila Damanik; Grace Purba; Klara Laoli; Bobby Delon Togatorop; Windy Suryani; Suvriadi Panggabean (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to estimate the water volume of Lau Kawar Reservoir using the cylindrical shell method of integral calculus. The reservoir is assumed to be a perfect cylinder with a radius of 564 meters and a depth of 8.45 meters. The volume is calculated using both the shell method and the standard analytical formula for cylinders. The result shows a water volume of 8,437,640.45 m³. Both methods produced identical results with an absolute error of 0.00 m³. This proves that the shell method is highly accurate for symmetrical reservoir shapes. The study demonstrates how integral calculus can be applied to real-world problems in hydrology.